Penerapan Ta’lim Al-Lugah Al-Arabiyyah Li Al-Agradh Al-Khassah Pada Fakultas Kedokteran dan Ilmu Kesehatan UIN Alauddin Makassar: Relasi Konstruktif Komponen Pembelajaran - Yunus, Purnamaniswaty (IAIN Bone, 2021)
The application of Ta'lim al-Lugah al-Arabiyyah li al-Agradh al-Khassah at the Faculty of Medicine and Health Sciences UIN Alauddin Makassar is oriented to intrioduce Arabic vocabularies relating to medicine and health sciences. The obstacles faced in the application of Ta'lim al-Lugah al-Arabiyyah li al-Agradh al-Khassah at the Faculty of Medicine and Health Sciences UIN Alauddin Makassar are the low ability of students related to Arabic and low interest in learning Arabic which is deep The solution needs to be done by strengthening constructive relations between learning components which in this case are learning objectives, learning syllabus, learning activities, the role of lecturers, the role of students, to the role of teaching materials with various implementation frameworks such as strengthening the adjusted Arabic learning objectives. with the scientific background of students which in turn is described in the learning syllabus, utilizing students who have better Arabic language skills in fostering their colleagues who still have low Arabic language skills, maximizing the role of lecturers as facilitators and the role of students as a personal negotiator alternatively, or creating learning activities and providing teaching materials that accelerate students' Arabic language skills accelerating their interest in learning Arabic.